Portomesenteric vein thrombosis following sleeve gastrectomy: Case report focusing on the role of pathogenetic factors. Issue 2 (March 2022) - Frattini, F.; Pino, A.; Matarese, A.; Carrano, FM; Gambetti, A.; Boni, L.; Ierardi, A.M.; Carrafiello, G.; Rausei, S.; Bertoli, S.; Dionigi, G.
Abstract: Introduction: Sleeve gastrectomy has currently become the most commonly performed bariatric. procedure worldwide according to the last IFSO survey, overtaking gastric bypass with. a share of more than 50% of all primary bariatric-metabolic surgery. Gastric leak, intraluminal bleeding, bleeding from the staple-line and strictures are the most common complications. Portomesenteric vein thrombosis (PMVT)after sleeve gastrectomy is. another complication that has been increasingly reported in case-series in recent.years, although it remains uncommon. In this case report is described an extended portomesenteric vein thrombosis after. sleeve gastrectomy interesting splenic vein too with a favorable course and an. uneventful follow-up. We try to search in this case for pathogenetic factors involved in. this complication. Case report: A 42-year old man, with a body mass index (BMI) of 45 kg/m2, with a medical history of Obstructive Sleep Apnea Sindrome (OSAS) underwent laparoscopic sleeve gastrectomy. Early postoperative course was uneventful. Six days after discharge he complained abdominal pain and was admitted at the Emergency Department. A CT scan with intravenous contrast showed an occlusion of the portal vein, of the intrahepatic major branches and an extension to the superior mesenteric vein and the splenic vein. The patient received heparin and oral anticoagulation together with intravenous hydration and proton pump inhibitors. Considering the favourable course the patient was discharged after six days with long-term oral anticoagulation therapy. Anticoagulation with acenocumarol was continued for six months after a CT scan showed resolution of the PMVT without cavernoma. He had no recurrence of symptoms. Discussion: Porto-mesenteric thrombosis after sleeve gastrectomy is a rare complication but it has been increasingly reported over the last 10 years along with the extensive use of sleeve gastrectomy. Because PMVT is closely associated with sleeve gastrectomy in comparison with other bariatric procedures, we need to investigate what pathogenetic factors are involved in sleeve gastrectomy. Thrombophylic state, prolonged duration of surgery, high levels of pneumoperitoneum, thermal injury of the gastroepiploic vessels during greater curvature dissection, high intragastric pressure, inadequate antithrombotic prophylaxis and delayed mobilization of the patient after surgery have been reported as pathogenetic factors of portmesenteric vein thrombosis. Most of the cases presented in the literature such as our clinical case resolve with medical therapy, although portal vein thrombus extends into the superior mesenteric vein and the splenic vein. Conclusion: Portomesenteric venous thrombosis is a rare but serious complication of bariatric surgery, especially associated with sleeve gastrectomy. Diagnosis is based on CT examination with intravenous contrast, and initial therapy is anticoagulation. Etiologic factors reported in the literature include a long duration of surgery, a high degree of pneumoperitoneum, high intragastric pressure after sleeve gastrectomy and thermal injury to the short gastric vessels and gastroepiploic arcade. Limited operative time, controlled values of pneumoperitoneum, careful dissection with energy device of gastric greater curvature, appropriate prophylaxis with low molecular weight heparin may be useful tools to prevent and limit this complication. Nonetheless we have to search which factors may condition the evolution of an extended PMVT as that described in this case towards resolution or to a further worsening clinical state. Early diagnosis? Correct treatment? Undiscovered patientrelated factors?